PATTERN OF PERFUSION DEFECTS SEEN IN ISCHEMIC HEART DISEASE PATIENTS ON TECHNETIUM (Tc99m) TETROFOSMIN SCANNING - Rahman, Abdul; Aftab, Jawed; Majeed, Rehan; Jaleel, Anila; Basir, Fasia; Shah, Sultan; Khan, RA (Journal of Ayub Medical College Abbottabad, 2005)
Background: Cardiovascular disease is common cause of death in developed as well as developing countries. The most common cause of Ischemic Heart disease is narrowing of coronary arteries, a process called as atherosclerosis. The objective of the present study is to determine the pattern of ischemic changes detected by technetium tetrofosmin (Tc99m). Methods: Sixty five patients presenting as known or suspected ischemic heart disease over a period of two years (December 1995 to December 1998) at Ziauddin Hospital were included in the study. Each patient underwent Tc99m tetrofosmin stress and rest studies. Tetrofosmin study was performed according to one day protocol. Results: By segmental analysis (five segment per patient), 35 patients had perfusion defects by SPECT Tc99m tetrofosmin imaging. Out of 95 perfusion defects, reversible ischemia and mixed defects were more common in inferior wall and fixed defect in left ventricular apex. Conclusion: Reversible ischemia and mixed defects were more common in inferior wall and fixed defect in left ventricular apex. Key words: Reversible, Ischemia, Imaging, Fixed Defects, Myocardial perfusion,